Virtual prediction of antiviral potential of ginger (Zingiber officinale) bioactive compounds against spike and MPro of SARS-CoV2 protein - Ahmad Hafidul Ahkam; Feri Eko Hermanto; Adzral Alamsyah; Iva Himmatul Aliyyah; Fatchiyah Fatchiyah (The East Java Biological Society, 2020)
Coronavirus disease 2019 (COVID-19) is a human disease caused by SARS-CoV2 becomes a serious health threat after infected more than 6 million people globally. The virus enters the host cell through an S protein on its surface and begins its life cycle with the help of a key protein, MPro. On the other hand, several bioactive from Ginger have been reported for their antiviral properties, but few studies related to COVID-19. This study aims to evaluate the potential of a few bioactive compounds from Ginger as anti-SARS-CoV2. Gingerenone A, gingerol, geraniol, shogaol, zingiberene, zingiberenol, and zingerone were used as ligand to be docked with S protein and MPro. Drug-likeness properties also evaluated using SwissADME. Gingerenone A constantly gave the lowest binding energy compared to others both with S or MPro. However, gingerol, geraniol, shogaol, zingiberene, zingiberenol, and zingerone could interact with key residues responsible for MPro catalytic domain, while geraniol, shogaol, zingiberene, zingiberenol, and zingerone could interfere S-ACE2 binding shape and increase its binding energy. The drug-likeness analysis also revealed that all of the analyzed compounds have no violation of Lipinski’s Rule of 5. In conclusion, gingerol, geraniol, shogaol, zingiberene, zingiberenol, and zingerone from Ginger have good potential as antiviral agents with good oral bioavailability and flexibility